EFEKTIVITAS HUKUM KEMITRAAN USAHA MINUMAN ARAK BALI DI DENPASAR - I Wayan Novy Purwanto; I Made Suryanata* (Fakultas Hukum Universitas Sjakhyakirti Palembang, 2022)
This study aims to understand and determine the regulation of the circulation of Balinese wine (Arak Bali) based on the Bali Governor Regulation Number 1 of 2020 and understand and determine the legal effectiveness of the Bali wine business partnership in Denpasar. The research method used is the type of empirical research with a statutory approach and a fact approach. The data source used is primary data from interviews with respondents and informants, while secondary data sources come from Bali Governor Regulation Number 1 of 2020, books and journals. The result of this study indicates that the regulation of the circulation of Balinese arak is determined in Articles 7 to 12. Furthermore, the circulation itself is experiencing chaos which can be seen from the development of the behavior of the people who produce Balinese wine personally and are not equipped with a distribution permit from the government. The sanctions specified are administrative sanctions.